EMPOWERING RESEARCH AND INNOVATION THROUGH RoViSP - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 2 February 2016 Today, we live in what is referred to as the Information Age or Digital Age of the 21 century. Automobiles, refrigerators, the Internet, World Wide Web, smart phones, tablet computers, and satellites are examples of hightechnology products that are part and parcel of daily 21 century living.